2019
DOI: 10.1080/21642850.2019.1691558
|View full text |Cite
|
Sign up to set email alerts
|

Successful ageing in older persons belonging to the Aymara native community: exploring the protective role of psychosocial resources

Abstract: Objectives: The aim of this study is to analyse the process of successful ageing in older persons who state their belonging to a native Chilean ethnic group. There has recently been a notable increase in interest regarding analysis of the cultural processes and variables associated with successful ageing. However, there is a lack of studies analysing successful ageing in native ethnic groups; that is, ethnic communities living in their natural environmental surroundings. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…Furthermore, having a positive attitude toward life including demonstrating forgiveness, optimism, belief in oneself, and embracing life, were seen as factors that contributed to aging well (15, 65, 66, 72-74, 76, 78, 79, 84, 90). Conversely, negative feelings of hopelessness, depression, and worry presented challenges to aging well (74,77,87,90). Three studies referred to older adults' feelings of being a burden on family and community (49,83,90).…”
Section: You Have Just To Pick Yourself Up and Keep Goingmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, having a positive attitude toward life including demonstrating forgiveness, optimism, belief in oneself, and embracing life, were seen as factors that contributed to aging well (15, 65, 66, 72-74, 76, 78, 79, 84, 90). Conversely, negative feelings of hopelessness, depression, and worry presented challenges to aging well (74,77,87,90). Three studies referred to older adults' feelings of being a burden on family and community (49,83,90).…”
Section: You Have Just To Pick Yourself Up and Keep Goingmentioning
confidence: 99%
“…To achieve health and wellbeing in later life, several factors were identified that contributed to the perception of aging well. Those factors included: maintaining spirituality ( 15 , 66 , 69 , 73 , 74 , 77 79 , 83 ); achieving emotional wellbeing ( 15 , 72 , 73 , 75 , 77 , 79 , 80 ); keeping cognitively engaged ( 66 , 73 , 76 , 83 – 85 ); staying active and busy ( 15 , 49 , 64 , 66 , 67 , 73 – 76 , 83 , 87 ); obtaining value and respect ( 15 , 66 , 68 , 73 , 75 , 77 , 78 , 89 , 90 ); and having a sense of purpose ( 83 , 88 , 90 , 94 ). Furthermore, the impact of the health and achievements of the wider family ( 71 , 73 , 85 ), being on traditional lands ( 15 , 63 , 71 , 73 , 80 , 81 , 84 , 87 ), engaging in subsistence lifestyles ( 66 , 67 , 71 , 75 , 84 ), and accessing traditional and healthy foods ( 15 , 66 , 69 , 70 , 73 , …”
Section: Synthesis Of Findingsmentioning
confidence: 99%
See 3 more Smart Citations